Efficacy and safety of artificial liver support system treatment for immune checkpoint inhibitors related liver failure in patients with hepatocellular carcinoma: Protocol for a randomized controlled clinical trial - Qiumin Luo; Yeqiong Zhang; Zhipeng Li; Jia Chen; Zhexuan Deng; Jiadi Lai; Xiyao Chen; Chan Xie; Liang Peng; Ying Liu; Wenxiong Xu (Heliyon)
Background: Immune checkpoint inhibitor-induced immune-mediated hepatitis (ICI-IMH) in patients with hepatocellular carcinoma (HCC) has been established to increase the risk of liver failure (LF). Given the accumulating evidence supporting the efficacy of artificial liver support systems (ALSS) in mitigating both IMH and LF, a single-center, non-blinded, randomized controlled clinical trial is proposed to investigate the efficacy and safety of ALSS for HCC patients with ICI-LF. Methods: and analysis: Sixty eligible participants will be enrolled in this trial and randomly assigned to one of two groups in a 1:1 ratio. In addition to standard pharmacological management, patients in the trial group will receive treatment with a double plasma molecular adsorption system (DPMAS) and low-volume plasma exchange (LPE) on three occasions, while patients in the control group will undergo PE three times. Patient assessments, including symptoms and laboratory tests, will be conducted at baseline, before and after the three ALSS treatments, and at 2, 4, 8, and 12 weeks post-enrollment. The primary outcome is the mortality rate at 12-week follow-up. Secondary outcomes include changes in the Model for End-Stage Liver Disease (MELD) score following ALSS treatment and the incidence of adverse events (AEs). Discussion: ICI-LF in HCC patients is associated with a high mortality rate and lacks effective treatment options. Our study aims to evaluate the efficacy and safety of ALSS for this patient population, comparing the effectiveness of two ALSS modalities (DPMAS + LPE vs. PE). Trial registration: This clinical trial has been registered on ClinicalTrials.gov with the identifier NCT05484908 (Release Date: July 30, 2022) (https://clinicaltrials.gov/study/NCT05484908).